The typomorphological façade of the catholic churches of S. Miguel - Vieira, Maria Antónia; Sampayo, Mafalda; Alves da Cunha, João (5 th International Conference of Contemporary Affairs in Architecture and Urbanism, 2022)
This research shows the analysis of the main facades of the catholic parish churches in the island of S. Miguel, Azores, built during the 18th and 19th centuries, and evidences the existence of a facade typology, through its similarities. This study develops an analysis of the matrix composition and ornamental elements present in the facades of 83 churches, mapping and characterizing the elements that compose them, grouping them into categories, allowing to establish and to synthesize a typology, called the micaelense model facade, according to the principles of composition present in the analyzed facades The analysis method, the reading of the forms of the facades of the churches, and the metric survey of these, were based on old and current photographic records, were supported by a comparative analysis elaborated and organized from tables and synthetic schemes systematized in vector drawings (graphic representations made in CAD).